2011
DOI: 10.5539/ijbm.v6n7p280
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Employees’ Commitment to Organisation through Training

Abstract: The role of training in human resource management practice has spur renewed and vigorous debate about the need for training and development. The debate has led academics and management to ponder on some issues germane to the benefits or otherwise of training. Is training an investment in people or cost? If training is required, what are the criterion used to determine who should be trained and when to train? These questions have permeated management circle and those in HRM department. Recent years have seen tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
0
6
1
Order By: Relevance
“…Third, whereas provision of training has been shown to be less important in the West, the results of this study demonstrate that in Malaysia it is important, as were similarly shown in other developing countries (Owoyemi, Oyelere, & Elegbede, 2011;Newman, Thanacoody, & Hui, 2011). The reason why the results obtained in Malaysia is different from the one in the West might be because employees in Malaysia are still technically immature in general and do not cause mismatch between the training a company provides and the skill an employee wants to obtain.…”
Section: Implications For Theory and Practicecontrasting
confidence: 44%
“…Third, whereas provision of training has been shown to be less important in the West, the results of this study demonstrate that in Malaysia it is important, as were similarly shown in other developing countries (Owoyemi, Oyelere, & Elegbede, 2011;Newman, Thanacoody, & Hui, 2011). The reason why the results obtained in Malaysia is different from the one in the West might be because employees in Malaysia are still technically immature in general and do not cause mismatch between the training a company provides and the skill an employee wants to obtain.…”
Section: Implications For Theory and Practicecontrasting
confidence: 44%
“…Third, whereas provision of training has been shown to be less important in the West in some previous research, the results of this study demonstrate that in Vietnam it is important, as were similarly shown in other developing countries (Newman, et al, 2011;Owoyemi, Oyelere, & Elegbede, 2011). The reason why the results obtained in Vietnam is different from the one in the West might be because employees in Vietnam are still technically immature in general and do not cause mismatch between the training a company provides and the skill an employee wants to obtain.…”
Section: Implications For Theory and Practicementioning
confidence: 56%
“…As specified by Meyer and Allen (1984), commitment is significantly determined by the richness of traditions and culture. In fact, organizational commitment is one of the most important factors in a company's performance since it illustrates the extent to which employees will engage with the company and complete the company's objectives (Owoyemi, Oyelere, Elegbede, & Gbajumo-Sheriff, 2011). This refers not only the loyalty that these employees show the company, but also their determination in completing tasks to obtain expected values (Messner, 2013).…”
Section: Impact Of Organizational Culture On Organizational Commitmentmentioning
confidence: 99%